2018
DOI: 10.1186/s42162-018-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards model-driven CIM-based data exchange for DSOs

Abstract: Smart energy systems (SES) promote the transformation of the distribution grid towards more sustainable operation and planning strategies, but also impose a set of considerable technological and political challenges. In this, distribution system operators (DSOs) are faced with the necessity of adapting their information system landscapes to enable the efficient utilization of information within their internal structures. In this work, we propose a model-based approach to derive an open middleware platform supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…In this paper we are starting from the existing protocols for electricity grids to validate that they are sufficient in realworld scenarios. Similar to [7], we conclude that the existing CIM standards can be used for the complementary use case of coordinated voltage control.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this paper we are starting from the existing protocols for electricity grids to validate that they are sufficient in realworld scenarios. Similar to [7], we conclude that the existing CIM standards can be used for the complementary use case of coordinated voltage control.…”
Section: Introductionsupporting
confidence: 66%
“…A common model of business and system roles and a common ontology should be used to identify the information that needs to be exchanged. In [7], a model based approach with a domain analysis of DSOs is used to derive the requirements on CIM profile and middleware for DSO applications. Both [5] and [6] point out that design principles and solutions developed for the Internet of Things (IoT) are beneficial to apply also for smart grids.…”
Section: Introductionmentioning
confidence: 99%
“…CIM: In the research project "ESOSEG" [9], a CIM-based model-driven framework was developed and demonstrated to enable standardized data exchange between various data systems for different services within a DSO company [44]. A similar CIM-based system architecture was used in [45] to develop a distribution system application platform based on CIM model conversion.…”
Section: Concepts For Des Data Model Integration In Dso Data Systemsmentioning
confidence: 99%
“…An overview of the existing legislation and standards for the communication and control of photovoltaic systems (PV) in different countries is provided in [5] (pp. [39][40][41][42][43][44], concerning the integration of PV in smart grids from a global perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Another solution provides data from various software systems installed at a distribution system operator via adapters. These adapters provide the data as a CIM data model through REST (Representational State Transfer) [25]. An alternative approach to increasing the interoperability of a grid operator is to create a reference architecture.…”
Section: Related Workmentioning
confidence: 99%